The relationship between nurses' risk assessment and management, fear perception, and mental wellbeing during the COVID-19 pandemic in Saudi Arabia - Al-Dossary, Reem N.; AlMahmoud, Sana; Banakhar, Maram Ahmed; Alamri, Majed; Albaqawi, Hamdan; Al Hosis, Khaled; Aljohani, Mohammed S.; Alrasheadi, Bader; Falatah, Rawaih; Almadani, Noura; Aljohani, Khalid; Alharbi, Jalal; et al. (Frontiers in Public Health, 2022)
Early interventions to help the nurses manage their mental well-being by providing them the information regarding coping skills and the same time preventive, risk assessment approach (e.g., hospital preparedness and rapid risk assessment) and ability to respond during this pandemic is greatly importance. This study evaluated the effect of risk assessment management to the mental well-being and fear of the nurses during the COVID-19 Pandemic in Saudi Arabia. A cross-sectional design survey was used with 507 nurses working in tertiary public hospitals in Saudi Arabia. A three survey scales were used namely: Risk Assessment scale, fear of COVID-19, mental well-being scale. Independent t-test and one-way ANOVA were used to examine the association between fear of COVID-19 and the demographic characteristics of nurses to their mental wellbeing. Multiple Regression analysis was performed to examine the predictors associated to mental wellbeing. Results showed that most of the participants have perceived moderate positive mental wellbeing with percentage 49.7% while only 14% had low levels of mental scale. Next, most of the respondents have low a low fear in COVID-19 level with percentage 45% while only 15% had high levels of fear scale. Then some demographic variable such as “Age”, “Nationality”, “Total years of experience in the current hospital”, and “Region, you work at” had statistical significance difference with P-value less than 0.5. Meanwhile, risk assessment is also associated with mental wellbeing scores. All items of Fear of COVID-19 Scale had no-significance difference with P-value more the 0.05.In conclusion, most of nurse’s provide direct care to a confirmed COVID-19 patient, state the importance of wearing PPE and perform hand hygiene before and after any clean or aseptic procedure. Meanwhile, although almost all nurses are vaccinated, they are still afraid of being infected with (COVID-19) while working with a positive patient and reported a low Fear of COVID-19 scores. Additionally, results reported that the older the nurses are, the better their mental-wellbeing scores, Non-Saudi nurses have higher perceived mental-wellbeing scores than Saudi nurses, different working environment correspond to different mental wellbeing scores. Finally, nurses risk assessment is associated with mental wellbeing scores.